The Effect of e-Service Quality And e-Satisfaction on e-Loyality at Mandar Coklat Shop Macoa - Azis, Fadli (Economics and Business Journal (ECBIS), 2023)
This study aims to find out how the effect of e-service quality on e-loyalty through e-satisfaction at Mandar Coklat Shop Macoa. The population in this study were customers at Mandar Coklat Shop Macoa the sample used was 60 customers. Data collection was carried out using the questionnaire method which was distributed via Google from. The data analysis technique used is partial least squares (PLS) using measurement model analysis (outer model) and structural model analysis (inner model) where the research results show a direct effect of E-Service (X) on E-Loyalty (Y), where from the results of the statistical test the result is a p-value (0.011) <0.05, which means that the p-value is less than the significance level of 0.05 so that there is a direct effect of E-Service on E -Loyalty.